Riddles in Schedules of Indian Wildlife (Protection) Act, 1972 in Need of Relook - Rajeev, B. M. T. (Indian Forester, 2017)
An attempt was made by me to indicate the Schedule numbers of the animals which have been described in my book (Hand Book of Indian Wild Animals- Kannada) to indicate their status of abundance/threats for their survival in India to the readers. Where in, I was struck with puzzle in the long list of invertebrates appended with scientific names&their respective families in Schedule-I of IWLPA,1972. I took one name of a butterfly and tried to check it's details in the web-site; to my surprise it led to its description and it was said to be found in Nandhi Hills-close to Bengaluru- the silicon city of Karnataka, India; still I could not find its English/Vernacular name to check it locally as it happens to be a spp of my native state; and it is difficult too to crosscheck with anyone other than an Entomologist. Then, I tried many names of insects from the said list; all led to the schedules of IWLPA only and couldn't find descriptions in the website. Whereas Schedule I, according to IWLPA, 1972 is the list of animals classified as rare, endangered and threatened with extinction and is in need of special protection in India. E.g. Tiger, elephant, Rhino, bison, leopard, sloth bear, whales, dolphins, python, pea-cock, sea-horse, scores of invertebrates/insects including dragon fly etc etc. The punishments prescribed for the crimes against the animals listed under different schedules too vary in the IWLP Act. This exercise of indicating the Schedule number against the name of the animals described in my book appeared to me as a puzzle and led me to pen this article.